(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The rare earth doped glass was the most valuable commodity and since the advent of optical communication, has drawn a great deal of medical and technological attention. In this analysis the glass and then glass elements, the identification of glasses and of rare earth ions, the structural properties of tellurite glass and rare earth doped glasses were discussed, and rare earth ions were given optical properties.